Nova abordagem da teoria de campo efetivo aplicada ao modelo de Ising com interações competitivas - Castro, Eronildo Cornélio de (2013)
The research of high temperature superconducting compounds formed by plans CuO2, has motivated the theoretical study in proposing a model able to describe their characteristics. In particular, these compounds have a common antiferromagnetic ordering, that for small doping, the Néel temperature is drastically reduced to zero when a critical concentration is reached pc. In this work, was used the randomly antiferromagnetic Ising model decorated with spin dfrac12 and competitive interactions to describe properties CuO2. This model consists of plans, in which the nodal spins interact antiferromagnetically J1 with its nearest neighbors (Cu - Cu interactions) and ferromagneticamente JF with the spins decorators (Cu - Ointeractions) that are randomly distributed ( textit quenched) over a three-dimensional network. It used the effective field theory based on operator technique for studying the differential phase transition in a cluster formed by two sites in a cubic lattice. The system was analyzed for the almost-twodimensional topologies and three-dimensional, initially, from the perspective of methodology Zernike, usually used in statistical mechanics, where you can analyze the phase diagram and the behavior of the magnetization. posteriorly, was applied a new methodological approach decoupling the model, which was analyzed only the phase diagram. Discussed the variation of the critical concentration Pc where the Néel temperature tends to zero for various values of the frustration parameter . For certain values of this parameter was observed reentrant behavior at low temperatures. Was calculated dependence of magnetization subnet as a function of temperature for analyzing the behavior observed in reentrant of phase diagrams.